Brand Awareness of New Brands among Youths- An Overview. - Goyal, Mohit; Khanna, Nandini; Sinha, Mitali; J.C, Dr. Sharmiladevi (The journal of contemporary issues in business and government, 2023)
In developing countries like India, the youth population is drastically increasing and with it- is the growing consciousness, awareness, and interest in fashion brands. The results showed that Indian youth is most responsive to brands that utilize video, graphic, and influencer marketing. Furthermore, this group also values and shows great brand awareness towards brands that stand by a cause. New brands that engage and interact with this audience are also appreciated. Peer reviews are also crucial to this group and peer recommendations drive brand awareness and purchases. The results showed that Gen Z primarily utilizes Instagram, and most brand awareness takes place on this platform as they are more receptive to ads on it. This generation also uses mobile devices for online shopping and browsing,signaling that new brands must pay close attention to developing mobile-friendly user interfaces.Generation Z in India is more open to modern western concepts like thrifting and gender-fluid fashion. However, this mindset shift is a relatively new phenomenon and is only present as firmly in some members of this group.